MEDIA EDUKASI VIDEO ANIMASI “CERDIK” DALAM PENCEGAHAN DIABETES MELITUS TIPE 2 DI SMAN 3 CIMAHI - Azzahra, Francisca; Karjatin, Atin (Jurnal Kesehatan Siliwangi, 2024)
Background: Diabetes melitus does not only occur in adulthood, but also occurs in adolescence. Data in Indonesia in 2018 with Diabetes melitus patients with the age category of 15 years amounted to 159,014 people. The number of cases in Cimahi City in 2018 was 3,601 cases, thus the need for knowledge of adolescents regarding the prevention of Diabetes melitus, so as to reduce the morbidity rate of non-communicable diseases. Based on the results of the research, animated video educational media can increase adolescent knowledge. Objective: To determine the feasibility of "CERDIK" animated video education media on the prevention of type 2 Diabetes melitus using the 4D approach. Method: to prove the feasibility of media use, a define, design, development approach is carried out with material tests, media tests, small-scale tests, and statistical tests with a quantitative approach using pre-experiments with a one-group pretest-posttest design on 81 students, and dissemination. Results: Analysis of the needs of students regarding the need for media in the form of animated videos, the resulting media is 4.33 minutes long, media development is feasible and has an effect on student knowledge, and the media can be accessed via links and Youtube. Conclusion: The educational media animated video is worth using and can be accessed at youtube.